2002
DOI: 10.1074/jbc.m207050200
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bacterium Prevents Cytokine-induced Apoptosis in Intestinal Epithelial Cells

Abstract: Probiotic bacteria are microorganisms that benefit the host by preventing or ameliorating disease. However, little information is known regarding the scientific rationale for using probiotics as alternative medicine. The purpose of this paper is to investigate the mechanisms of probiotic beneficial effects on intestinal cell homeostasis. We now report that one such probiotic, Lactobacillus rhamnosus GG (LGG), prevents cytokineinduced apoptosis in two different intestinal epithelial cell models. Culture of LGG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
338
1
18

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(364 citation statements)
references
References 43 publications
(44 reference statements)
7
338
1
18
Order By: Relevance
“…[20][21][22] Proposed mechanisms for probiotic-induced protection from apoptosis include activation of the anti-apoptotic Akt/protein kinase B and also through inhibition of the pro-apoptotic p38/mitogen activated protein kinase. 19 It was interesting to note that apoptosis was reduced only in the rats which received VSL#3 both before and following irinotecan. This may indicate that VSL#3 works in two ways to prevent cell death following chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22] Proposed mechanisms for probiotic-induced protection from apoptosis include activation of the anti-apoptotic Akt/protein kinase B and also through inhibition of the pro-apoptotic p38/mitogen activated protein kinase. 19 It was interesting to note that apoptosis was reduced only in the rats which received VSL#3 both before and following irinotecan. This may indicate that VSL#3 works in two ways to prevent cell death following chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by the work carried out by Yan and Polk. 19 They showed that probiotic treatment prevents intestinal epithelial cell apoptosis in response to tumour necrosis factor (TNF), interleukin-1 alpha (IL-1a) and g interferon (IFN). 19 These pro-inflammatory factors have been implicated in the pathogenesis of chemotherapy-induced mucositis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ligand-specific activation of the TLR2 system greatly enhance transepithelial resistance in IEC lines associated with apical tightening and sealing of tight junction-associated ZO-1. 45 In addition, Yang and Polk suggested that L. rhamnosus GG inhibits tumour necrosis factor (TNF)-mediated pro-apoptotic mechanisms in IEC YAMC cultures through the blockade of TNF-induced p38 MAPK activation 46 . Interestingly and consistent with our data, one mechanism to trigger antiapoptotic signalling pathways includes the induction of the NF-jB signalling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…In fact: (1) probiotics modulate and stabilize the composition of the microbiota and, therefore, may have immunomodulatory effects; (2) some probiotics are able to inhibit the inflammatory response of the intestinal immune system through inhibition of NF-B activation or in combination with an anti-apoptotic action on intestinal epithelial cells [31,32]; (3) some probiotics are able to increase the activity of Natural Killer (NK) cells [33,34], which are first line of defense as they can perform cytotoxic activities independent from prior sensitization to antigens; (4) some probiotics increase the secretion of mucus [22]; (5) some probiotics have a direct immunomodulatory action: after being captured in the Peyer's patches, they can induce the secretion of cytokines and the expression of co-stimulatory molecules by antigen presenting cells (APC) [35]; (6) some strains of lactobacilli induce dendritic cells (DC) maturation [36]. DC can, through their particular cytostructure, pass through the layer of epithelial cells and capture antigens directly from the lumen.…”
Section: Probiotics and The Immune Responsementioning
confidence: 99%